Revealing Teachers’ Methods in Teaching Test of English as Foreign Language (TOEFL) - Maharani, Sinta; Miftachudin, Miftachudin (Journal of English Teaching and Learning Issues, 2021)
This study aims to investigate Teachers’ methods and find out the most common use method in teaching TOEFL in International Class Program (ICP) of IAIN Salatiga. This qualitative research applies interviews and documentation in populating data. The data were derived from lecturers’ journals on teaching TOEFL from 2010 to 2020 and probed the details on the interview session with the lecturers of TOEFL in ICP of IAIN Salatiga. The researcher found there were ten methods namely Synchronous and Asynchronous Method, Autonomous Learner Method, Drill and Practice Method, Error Analysis Method, Games Based Learning Method, Inquiry-Based Instruction Method, Questions & Answers Method, Mind Mapping Method, and Communicative Language Teaching (CLT) Method. The most common use methods in teaching TOEFL are Drill and Practice Method, and Discussion Method. The result of this study provides the teachers’ insight in teaching TOEFL effectively.